Evangelização das classes médias e solidariedade com os pobres: o legado de Medellín - Morás, Francisco (Revista eclesiástica brasileira, 1998)
After a brief historical-ecclesiastical contextualization of the document of Medellín, the author, in this article, offers a threefold analysis of the document. In the first place, it evidences the principal components ofthe project for evangelization present in the document, followed by an evaluation on how the middle classes, directly or indirectly, enter into this project of evangelization and, to sum up, a try at deducing the leveis of solidarity with the poor that we can expect from the middle classes. This is about an analysis motivated by the suspician that the solidarity with the poor depends, in great measure, upon the quality of the evangelization that was ministered to the middle classes.